Pengaruh Model Project Based Learning Berbantuan Media Audio Visual dan Minat Terhadap Menulis Teks Prosedur - Isesma Zurita; Syofiani Syofiani; Hasnul Fikri (AHKAM, 2026)
Although the teaching of procedural text writing has been addressed in previous studies, research that specifically examines the interaction between the Project-based Learning (PjBL) model supported by audio-visual media and students’ learning interest in relation to learning outcomes remains limited. This study aimed to describe the influence of the PjBL model supported by audio-visual media and learning interest on students’ learning outcomes in writing procedural texts. This quantitative study employed a quasi-experimental design involving 52 students selected through total sampling. Data were collected using a performance test on procedural text writing and a learning interest questionnaire, and were analyzed using t-tests and two-way ANOVA. The findings indicated a significant difference in procedural text writing outcomes between the class taught using the PjBL model supported by audio-visual media and the class taught using conventional instruction (t_calculated = 6.016 > t_table = 2.009). These findings contribute to strengthening constructivist theory and extend understanding of the use of innovative instructional media in the development of writing skills. The study concludes that implementing the PjBL model supported by audio-visual media in teaching procedural text writing is crucial, and encourages educators to integrate this model to enhance students’ motivation and learning outcomes, with theoretical implications for the Indonesian language education literature and practical implications for schools in optimizing the use of audio-visual media.